Open Learning Environment Based Service Learning(Sl) (Study Theory, Model And Learning Strategy - Nurbaya Nurbaya; Sukardi Abbas; Sun Hi Obu (IAIN Ternate, 2020)
Learning innovations continue to be carried out in order to fulfill the learning curve. These innovations have spawned a variety of models, approaches, strategies and learning methods. From teacher-dominated learning to actively engaging learners. This paper systematically reviews and discusses several scientific works. The results revealed that the service learning environment is a product of learning innovation, namely the acquisition of knowledge based on critical thinking, personal experience and ability and active involvement in addressing problems in the community or community. This model and strategy was born from the theory of association learning, namely open learning that focuses on self-inquiry, divergent thinking and heuristics-based learning).Keywords: Open learning environment, Service Learning